Flexible fabric-based electrochemical biosensor for continuous measurement of glucose concentration - Aldi Michi, 1992- 637429; Dedy H. B. Wicaksono, supervisor 637430; Fakulti Biosains dan Kejuruteraan Perubatan 538915 (2015)
Project Paper (Sarjana Muda Kejuruteraan (Bio - Perubatan)) - Universiti Teknologi Malaysia, 2015